Elements of marketing - Alminar-Mutya, Ruby F. (Mandaluyong City, Philippines : National Book Store, 2000)
Principles, practices and systems are explained using the elements of the marketing mix, where the components are arranged accordingly per chapter.
1. The Marketing Systems: its Nature and the Elements -- 2. The Product -- 3. Pricing objectives and price determination -- 4. Channels of distribution -- 5. Physical Distribution System -- 6. Promotional Mix -- 7. Consumer Education within the Philippine Context -- 8. Consumers cooperatives -- 9. Relationship Marketing and Marketing Communication -- 10. Global Marketing.
Includes bibliographical references.
Keywords: MARKETING